The Design of the Measuring Tool of Clamping Force on E Clip Rail Fastening Systems - Rusman Prihatanto; Adya Aghastya; Dimas Faisal Maulana; Risma Fauziah Rahmawati; Afif Navir Refani (Journal of Railway Transportation and Technology, 2023)
The rail fastening system is a core component to fastening a rail on the railway sleeper to make it strong and solid. The position of the railway sleeper probably could move by the effect of the dynamic movement of railway wheels on the railroad. Elastic fastening which has a clamping force of 900-1100 kgf (kilogram-force) for each clip is one of the elastic fastening types. The deflection of Pandrol E-Clip is between 11,5 – 14 mm with the clamping force as 0,6 – 1,1 ton. The degradation of clamping force on fastening systems inevitably occurs by its use and regular railways operation. This study aims to create a strong, solid, and easy-to-operate measuring tool for clamping force on type E clip fastening systems. The design of the measuring tool of clamping force on type E clip fastening uses Solidworks software. After testing the measuring tool of clamping force on type E clip fastening systems, it shows that it is solid, countable and there is no form-change and damage on it. The design of that measuring tool can be effectively operated by two officers and it has 850 mm in height, and 270 m in width, and its weight including load cell and indicator reaches 17,83 kg. The function test on the measuring tool of the E-Clip fastening shows an average score of 1589,40 – 1682,50 kgf of clamping force. The result of clamping force measurement on the fastening by using a designed measuring tool is bigger than the need of clamping force of installed fastening namely 915,71 kgf.